ENVIRONMENTAL TAXES AS INSTRUMENTS IN THE ENVIRONMENTAL PROTECTION POLICY OF THE EUROPEAN UNION – SPECIAL EMPHASIS ON THE ECOLOGICAL COMPONENT DURING TAXATION OF MOTOR VEHICLES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
Environmental protection is one of the basic priorities of modern states. The CO2 emissions from motor vehicles are one of the main environmental threats. Ecological taxes have an important role to play in the commitment for reducing CO2 emissions. The vehicle taxation system is very different between the member states of the European Union, with an accentuated complexity within each country, based on the environmental and energy characteristics of the vehicles. This paper aims to analyze the system of taxation of motor vehicles within the legal systems of the member states of the European Union, with special emphasis on the legal framework of the Republic of North Macedonia, and its environmental and fiscal implications.
Keywords: Environmental protection, ecological taxes, European Union, motor vehicles, Republic of North Macedonia